A model providing long‐term data sets of energetic electron precipitation during geomagnetic storms. Issue 20 (26th October 2016) - van de Kamp, M.; Seppälä, A.; Clilverd, M. A.; Rodger, C. J.; Verronen, P. T.; Whittaker, I. C.
Abstract: The influence of solar variability on the polar atmosphere and climate due to energetic electron precipitation (EEP) has remained an open question largely due to lack of a long‐term EEP forcing data set that could be used in chemistry‐climate models. Motivated by this, we have developed a model for 30–1000 keV radiation belt driven EEP. The model is based on precipitation data from low Earth orbiting POES satellites in the period 2002–2012 and empirically described plasmasphere structure, which are both scaled to a geomagnetic index. This geomagnetic index is the only input of the model and can be either D s t or A p . Because of this, the model can be used to calculate the energy‐flux spectrum of precipitating electrons from 1957 ( D s t ) or 1932 ( A p ) onward, with a time resolution of 1 day. Results from the model compare well with EEP observations over the period of 2002–2012. Using the model avoids the challenges found in measured data sets concerning proton contamination. As demonstrated, the model results can be used to produce the first ever >80 year long atmospheric ionization rate data set for radiation belt EEP. The impact of precipitation in this energy range is mainly seen at altitudes 70–110 km. The ionization rate data set, which is available for the scientific community, will enable simulations of EEP impacts on the atmosphere and climate with realistic EEP variability. Due to limitations in this first version of the model, the results most likely represent an underestimation of the total EEP effect. Key Points: A model for radiation belt energetic electron precipitation (30‐1000 keV) has been developed It can be used to calculate the energy‐flux spectrum of precipitating electron from 1932 to present The results can be used to produce the first >80 year long atmospheric ionization rate data set